Gender differences in perceived stress and coping among college students - Graves, B. Sue; Hall, Michael E.; Dias-Karch, Carolyn; Haischer, Michael H.; Apter, Christine (PLOS ONE, 2021)
Background Many college students register each semester for courses, leading to productive careers and fulfilled lives. During this time, the students have to manage many stressors stemming from academic, personal, and, sometimes, work lives. Students, who lack appropriate stress management skills, may find it difficult to balance these responsibilities. Objectives This study examined stress, coping mechanisms, and gender differences in undergraduate students towards the end of the semester. Design and method University students (n = 448) enrolled in three different undergraduate exercise science courses were assessed. Two instruments, the Perceived Stress Scale and Brief Cope, were administered during the twelfth week of the semester, four weeks prior to final exams. T-tests were used to detect gender differences for the stress levels and coping strategies. Results Overall, females indicated higher levels of stress than their male counterparts. Gender differences were evident in both coping dimensions and individual coping strategies used. Females were found to utilize the emotion-focused coping dimension and endorsed the use of four coping strategies more often than males. These included self-distraction, emotional support, instrumental support, and venting. Conclusions This research adds to the existing literature by illuminating the level of perceived stress and different coping strategies used by undergraduate female and male students. In turn, students may need educational interventions to develop effective and healthy coping strategies to last a lifetime. Faculty and other university officials may want to highlight and understand these various factors to protect the students’ wellbeing in their classes.